Communication Factors In Policy Implementationpoverty Reduction In Maluku Province In 2023 - Diah Elvira Melanti Kiat; Chanif Nurcholis; Mohamad Arsad Rahawarin (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
This research aims to identify and analyze the communication factor in the implementation of poverty reduction policies in Maluku Province in 2023. This study employs a qualitative approach, adopting the theory of Edward III, where policy implementation is based on four factors: communication, resources, disposition, and bureaucratic structure. However, the main focus discussed in this research is the communication factor. Data collection was conducted using in-depth interviews with several key informants from local government in Maluku Province, including the Social Service, Education Service, Health Service, Industry and Trade Service, Manpower and Transmigration Service and the Regional Development Planning Agency. The results indicate that the implementation of poverty reduction policies in Maluku Province generally still requires improvement in terms of communication. It is imperative for the government to strengthen and intensify communication and coordination between policy-makers and the targeting of the policy. This crucial step is necessary to realize the intended and successful outcomes of the poverty reduction program implementation in Maluku.